Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài 1:
a, 58.32 + 58.68 - 800
= 58.(32 + 68) - 800
= 58.100 - 800
= 5800 - 800
= 5000
b, 12020 + 280 : [55 - (7 - 4)3]
= 12020 + 280 : [ 55 - 33 ]
= 12020 + 280 : [ 28]
= 12020 + 10
= 12030
c, (96 - 19 - 45) - (55 + 96 - 119)
= 96 - 19 - 45 - 55 - 96 + 119
= (96 - 96) + (119 - 19) - (45 + 55)
= 0 + 100 - 100
= 0
\(a,14-5+x=30\)
\(\Rightarrow9+x=30\Rightarrow x=30-9\)
\(\Rightarrow x=21\)
\(b,45-\left(3+x\right)=14\)
\(\Rightarrow3+x=45-14\)
\(\Rightarrow3+x=31\Rightarrow x=31-3\)
\(\Rightarrow x=28\)
\(c,18+\left(-3+x\right)-\left(44-x\right)=55\)
\(\Rightarrow18-3+x-44+x=55\)
\(\Rightarrow2x-29=55\Rightarrow2x=55+29\)
\(\Rightarrow2x=84\Rightarrow x=84:2\)
\(\Rightarrow x=42\)
\(d,\left(x-45\right).27=0\)
\(\Rightarrow x-45=0\Rightarrow x=45\)
a) 10+2x=45:43
10+2x=42
10+2x=16
2x=16-10
2x=6
x=6:2
x=3
vậy x=3
b)130-(100+x)=25
100+x=130-25
100+x=105
x=105-100
x=5
vậy x=5
c)22.(x+32)-5=55
4.(x+9)=55+5
x+9=60:4
x+9=15
x=15-9
x=6
vậy x=9
d)72-7(13-x)=14
49-7(13-x)=14
7(13-x)=49-14
13-x=35:7
13-x=5
x=13-5
x=8
vậy x=8
a)23+3 𝑥 =125 | b) 70 – 5.(𝑥 - 3)= 45 | c) 20 + 5 𝑥 = 57:55
3 𝑥 +23=125 | 70−5 𝑥 +15=45 | 5 𝑥 +20=5755
𝑥=34 | 𝑥=8 | 𝑥=−104
275
a,(x-15)-75=0
x-15 =75
x =75+15
x =90
b,72-(6.x+5)=55
6.x+5=72-55
6.x+5=17
6.x=17-5
6.x=12
x=12:6
x=2
c,575-(6.x+70)=445
6.x+70=575-445
6.x+70=130
6.x=130-70
6.x=60
x=60:6
x=10
d,(x-34).15=0
x-34=0
x=34
e,15+(18-x)=26
18-x=26-15
18-x=11
x=18-11
x=7
g,(x-5):16=2
x-5=2.16
x-5=32
x=32+5
x=37
1) 70 - 5( x - 3 ) = 45
5( x - 3 ) = 70 - 45
5( x - 3 ) = 25
x - 3 = 25 : 5
x - 3 = 5
x = 5 + 3
x = 8
2) 12 + ( 5 + x ) = 20
5 + x = 20 - 12
5 + x = 8
x = 8 - 5
x = 3
3) 130 - ( 100 + x ) = 25
100 + x = 130 - 25
100 + x = 105
x = 105 - 100
x = 5
4) 175 + ( 30 - x ) = 200
30 - x = 200 - 175
30 - x = 25
x = 30 - 25
x = 5
5) 5( x + 12 ) + 22 = 92
5( x + 12 ) = 92 - 22
5( x + 12 ) = 70
x + 12 = 70 : 5
x + 12 = 14
x = 14 - 12
x = 2
6) 95 - 5( x + 2 ) = 45
5( x + 2 ) = 95 - 45
5( x + 2 ) = 50
x + 2 = 50 : 5
x + 2 = 10
x = 10 - 2
x = 8
7) 14x + 54 = 82
14x = 82 - 54
14x = 28
x = 28 : 14
x = 2
8) 15x - 133 = 17
15x = 17 + 133
15x = 150
x = 150 : 15
x = 10
9) 155 - 10( x + 1 ) = 55
10( x + 1 ) = 155 - 55
10( x + 1 ) = 100
x + 1 = 100 : 10
x + 1 = 10
x = 10 - 1
x = 9
d,155-10(x+1)=55
10(x+1) = 155 - 55
10(x+1) = 100
x+1 = 100 : 10
x+1 = 10
x = 10 - 1 =9
e,6(x+\(2^3\))+40=100
6(x+\(2^3\)) = 100 - 40
6(x+\(2^3\)) = 60
(x+\(2^3\)) = 60 : 6
(x+\(2^3\)) = 10
x = 10 - \(2^3\)
x = 10 - 8 = 2
f,\(2^2\)(x+\(3^2\))-5=55
\(2^2\)(x+\(3^2\)) = 55 + 5
\(2^2\)(x+\(3^2\)) = 60
(x+\(3^2\)) = 60 : \(2^2\)
(x+\(3^2\)) = 60 : 4
(x+\(3^2\)) = 15
x + 9 = 15
x = 15-9=6.
Hok tốt !
d) \(155-10\left(x+1\right)=55\)
\(\Rightarrow10\left(x+1\right)=155-55\)
\(\Rightarrow10\left(x+1\right)=100\)
\(\Rightarrow x+1=100:10\)
\(\Rightarrow x+1=10\)
\(\Rightarrow x=10-1\)
\(\Rightarrow x=9\)
Vậy x = 9
e) \(6\left(x+2^3\right)+40=100\)
\(\Rightarrow6\left(x+2^3\right)=100-40\)
\(\Rightarrow6\left(x+2^3\right)=60\)
\(\Rightarrow x+2^3=60:6\)
\(\Rightarrow x+2^3=10\)
\(\Rightarrow x+8=10\)
\(\Rightarrow x=10-8\)
\(\Rightarrow x=2\)
Vậy x = 2
f) \(2^2\left(x+3^2\right)-5=55\)
\(\Rightarrow2^2\left(x+3^2\right)=55+5\)
\(\Rightarrow2^2\left(x+3^2\right)=60\)
\(\Rightarrow4\left(x+9\right)=60\)
\(\Rightarrow x+9=60:4\)
\(\Rightarrow x+9=15\)
\(\Rightarrow x=15-9\)
\(\Rightarrow x=6\)
Vậy x = 6
Bài 1:
a) 17-25+55-17
=(17-17)+(-25+55)
=0+30
=30
b.(-37+101)-(91+37)
= -37+101-91-37
=(-37-37)+(101-91)
= -74 + 10
=-64
c.(-4-6):(-5)
=(-10) : (-5)
=2
d)35-(-95)+372-(372+95)
=35+95+372-372-95
=35+(95-95) + ( 372-372)
=35
a/ 22(x + 32) - 5 = 55 b/ 155 - 10(x+1) = 55
4(x + 32) = 60 10(x + 1) = 100
x + 32 = 60 : 4 x + 1 = 10
x + 32 = 15 x = 10 - 1
x = 15 - 32 x = 9
x = - 17
c/ 5. 22 + (x+3) = 52 53 - 5 (4 + x) = 15
20 + (x+3) = 25 125 - 5(4 +x) = 15
x+ 3 = 5 5(4 + x) = 110
x = 5-3 4 + x= 110 : 2
x = 2 4 + x = 55
x = 51
ủng hộ mk nha !!!! ^_^
45 + ( x - 6 ) . 3 = 60
x-6 = (60-45):3 = 5
x = 5+6 = 11
392 + ( 12 + 3 . x ) . 6 = 404
12+3.x = (404-392):6 =2
3x = 2-12 = -10
x = -10/3
17 . x + x - 4x = 70
x.( 17+1-4) = 70
x .14 = 70
x = 70:14 =5
( 2 . x + 42 ) . 93 = 2 . 94
2.x +16 . = 2.94 :93 = 2 .9 = 18
2x = 18-16 = 2
x = 2:2 =1
49 - 5 . ( 7 - x ) = 29
7-x = (49-29) :5 = 4
x = 7-4 =3
12 . x + 19 . x - 123 = 280
x . ( 12+19) = 280-123 =157
x . 31 = 157
x = 157:31 = 157/31
a: \(2^2\left(x+3^2\right)-5=-55\)
=>\(4\left(x+9\right)=-55+5=-50\)
=>\(x+9=-\dfrac{50}{4}=-\dfrac{25}{2}\)
=>\(x=-\dfrac{25}{2}-9=-\dfrac{43}{2}\)
b: \(\left(-70\right)\cdot x=280\)
=>\(x=\dfrac{280}{-70}\)
=>x=-4
(-70). x = 280
x = 280 : (-70)
x = -4